1997
DOI: 10.1001/jama.1997.03540290035029
|View full text |Cite
|
Sign up to set email alerts
|

Major Depressive Disorder in the 6 Months After Miscarriage

Abstract: Physicians should monitor miscarrying women in the first weeks after reproductive loss, particularly women who are childless or who have a history of major depressive disorder. Where appropriate, supportive counseling or psychopharmacologic treatment should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
1
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(65 citation statements)
references
References 27 publications
1
58
1
5
Order By: Relevance
“…Several clinical studies reported that miscarriage causes mental distress such as depression, anxiety, anger, and grief. [8][9][10][11][12][13][14][15][16][17][18][19][20] All of these studies have focused on abortions which resulted with early pregnancy loss such as spontaneous abortion, induced abortion and recurrent abortion. However, there is no comprehensive study specific to psychological morbidities such as anxiety and depression disorders in patients with TA.…”
mentioning
confidence: 99%
“…Several clinical studies reported that miscarriage causes mental distress such as depression, anxiety, anger, and grief. [8][9][10][11][12][13][14][15][16][17][18][19][20] All of these studies have focused on abortions which resulted with early pregnancy loss such as spontaneous abortion, induced abortion and recurrent abortion. However, there is no comprehensive study specific to psychological morbidities such as anxiety and depression disorders in patients with TA.…”
mentioning
confidence: 99%
“…Results from a variety of cross-sectional and prospective longitudinal studies indicate the sense of loss may be ongoing (Garel, Blondel, LeLong, Bonenfant, & Kaminski, 1994;Neugebauer et al, 1997;Robinson, Stirtzinger, Stewart, & Ralevski, 1994). Hutti, dePacheco, and Smith (1998) surveyed 186 women who said that their miscarried babies were ''real.''…”
mentioning
confidence: 99%
“…When pregnancy ends prior to the point of expected fetal viability, most investigators have not been able to document an association between length of gestation and intensity or duration of grief, anxiety, or depression (Jackman, McGee, & Turner, 1991;Neugebauer et al, 1997;Prettyman et al, 1993;Thapar & Thapar, 1992). Yet, other investigators have found evidence that gestational age at miscarriage may influence responses.…”
mentioning
confidence: 99%
“…Somewhat consistent results are found when level of grief after miscarriage and the presence of prior psychiatric symptoms are studied, with preloss coping capacity seeming to be predictive of level of grief. Finally, the absence of studies on the effects of social support and religious participation on level of grief following miscarriage prevents any conclusions from being drawn [37][38][39][40][41][42][43][44][45] .…”
Section: Results Of the Reviewmentioning
confidence: 99%